Mobility schemes in clustered proxy mobile IPv6 - Al-Humrany, Adnan Jumaa Jabir (2015)
IP-based Wireless Sensor Networks (IP-WSNs) provide a tremendous potential to improve the capabilities of many systems, for instance, healthcare, home automation, environmental monitoring, industrial control, agricultural monitoring, and motivating the rise of the Internet of Things (IoT) paradigm where different devices are connected to the Internet with no or minimal human involvement. Mobility management protocols are very essential in the new research area of IoT. This is mainly due to the static attributes of nodes are no longer dominant in the current and emerging applications. It should provide users with full access to information irrespective to their locations while preserving the sensor nodes energy and system reliability. Sensor Proxy Mobile IPv6 (SPMIPv6), which is an adaptation of the network based basic PMIPv6 protocol, was designed for IP-WSNs mobility management to save sensors energy consumption by relying the mobility process on the network entities, named Local Mobility Anchor (LMA) and Mobility Access Gateways (MAGs), to relieve the sensor nodes from participating in the handoff process. However, SPMIPv6 inherited most of the problems observed in PMIPv6 protocol, including long handoff latency because all the binding update messages are processed by LMA, non-optimized communication path because all data packets are obligated to pass through LMA, the lack of buffering scheme that is important to reduce the packet loss during handoff, and bottleneck issues in the LMA. Previous work enhanced the PMIPv6 performance in many directions by applying fast handoff and route optimization mechanisms. However, previous schemes are either proposed multiple LMA domains, built on the host based principles which involves the MNs in the mobility process, or it incurs a high signaling cost due to the requirement for exchanging extra control messages and rely the mobility process on the far LMA. The goals of this thesis are: firstly, to develop an enhanced architecture for SPMIPv6 called Clustered PMIPv6 (CPMIPv6) to overcome the problems in the existing solutions. In the proposed architecture, the MAGs are grouped into clusters, each with a distinguished cluster head MAG (HMAG). The HMAG is mainly introduced to reduce the load on LMA by performing intra-cluster handoff signaling and providing an optimized path for data communications. Secondly, to develop a new fast handoff scheme based on the CPMIPv6, in which, the HMAGs carry out the intra-cluster handoff to reduce both the handoff signaling, packet loss ratio and the buffered packets delay. Thirdly, to develop a new route optimization scheme for the CPMIPv6, in which, the HMAGs are utilized to reduce the handoff latency while achieving a fast recovery of the optimized path after handoff. Thorough analytical models and simulations using the Network Simulator (NS2) are developed and used for evaluating the performance of the proposed schemes compared with standard PMIPv6, SPMIPv6, state-of-the-art fast handoff and route optimization schemes. The numerical and simulation results show that the proposed model and schemes enhanced the overall performance by reducing of the load on LMA through relying the intra-cluster operations on the HMAGs, shortening the transmission path by excluding the LMA from participating in the intra-domain transmission process, reducing the handoff latency, and hence reducing the buffered packets delay. However, in some circumstances when MNs generate a high inter-cluster mobility or inter-domain communications, the protocol performance is degraded and the PMIPv6 problems are emerged again.